The Role of School Principals in Improving Teacher Competence at Madrasah Aliyah Negeri Palopo - Mahadin Saleh; Hasbi Hasbi; Radhiah Radhiah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
This study aims to analyze the role of school principals in improving teacher competence in Madrasah Aliyah Negeri Palopo. This research is qualitative. The author uses several theories in explaining the phenomenon and interpreting the data found. This research was conducted at Madrasah Aliyah Negeri (MAN) Palopo, 2014-2015 Academic Year. Sources of research data were obtained through two channels, namely primary data sources and secondary data sources. The subjects of this study were the principal at Madrasah Aliyah Negeri (MAN) Palopo, who was in office when this research was conducted, and the teachers. They were selected to provide information about the role of the principal in improving teacher competence at Madrasah Aliyah Negeri (MAN) Palopo. This research data collection through observation, interviews, and documentation. The results of the study found that madrasa management at Madrasah Aliyah Negeri Palopo can be seen from the role of the head of Madrasah Aliyah Negeri Palopo as a manager in managing institutions, which include: curriculum management, personnel management, student management, financial management, and management of school facilities and infrastructure, the pattern of approach The activities carried out by the Madrasah Head towards improving teacher competence in the public Madrasah Aliyah (MAN) Palopo is by compiling programs and coordinating with teachers, being active in training and improving educational qualifications, carrying out teacher competency testing activities, implementing a culture of discipline with tightened attendance, providing motivation to teachers, and activate teacher organization activities.